Time Management Training in Improving Students' Self Regulated Learning - Haryati, Siti; Amrulloh, Abdul Afif; Lestari, Sri (Prosiding University Research Colloquium, 2022)
The learning process is an activity carried out by every human being, students carry out the learning process at school by following directions from schools and teachers to achieve the goals desired by students. This training aims to improve self-regulated learning in students. The participants of this training were 10 SMA X students. There were 3 stages in this training, namely, the pretest stage, the training stage, and the posttest stage as the last stage. The results of the training showed that there was a positive correlation between the pretest and posttest. The results of the analysis of the value of t = -2.744 and p <0.05, it can be concluded that the implementation of time management by recording study schedules has an effect on students' self-regulated learning. In conclusion, time management training can improve self-regulated learning.